1998
DOI: 10.1002/(sici)1099-1395(199802)11:2<149::aid-poc983>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations on P?C bond cleavage in phosphoranyl radicals: implications for the biodegradation of organophosphonate derivatives

Abstract: Barrier heights for P-C bond homolysis in P-hydroxy-P-methyl-P,P-dioxophosphoranyl and P,P,Ptrihydroxy-P-methylphosphoranyl were calculated using well correlated levels of electronic structure theory. The best estimate for the difference in barriers between the two indicates that homolysis is more facile for P,P,P-trihydroxy-Pmethylphosphoranyl by roughly 9 kcal mol À1 . This result suggests that bacterial pathways leading to P-C bond cleavage in organophosphonate derivatives will preferentially proceed via in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…While there is more general agreement between the MP2 and the B3LYP results, significant discrepancies arise in several instances, most of which are discussed further below. We consider the MP2 level to be more reliable, given the known tendency of DFT to “over-delocalize” charge , and spin, , which can be an issue in some of the systems described below. Single-point calculations at the CCSD or CCSD(T) levels of theory for select instances bear this analysis out, and we therefore largely confine the discussion below to MP2 results.…”
Section: Resultsmentioning
confidence: 99%
“…While there is more general agreement between the MP2 and the B3LYP results, significant discrepancies arise in several instances, most of which are discussed further below. We consider the MP2 level to be more reliable, given the known tendency of DFT to “over-delocalize” charge , and spin, , which can be an issue in some of the systems described below. Single-point calculations at the CCSD or CCSD(T) levels of theory for select instances bear this analysis out, and we therefore largely confine the discussion below to MP2 results.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that, in some instances, an additional “ligand π” structure (IV), in which the unpaired electron was carried by one of the ligands (usually a phenyl group), is possible. More recently, ab initio molecular orbital studies have confirmed these electronic structure assignments and provided an insight into the mechanisms for ligand permutation , The apicophilicity of a variety of ligands has been found to depend mainly on their group electronegativities, though other factors (such as the potential for hyperconjugative interactions between the ligands 11 ) are also important.…”
Section: Introductionmentioning
confidence: 94%
“…Despite the fact that aminophosphonates are rather stable compounds, their P−C bond cleavage was observed in basic, neutral, and acidic media. These cleavage reactions are also catalyzed by enzymes in living organisms. , The P−C bond breaking generally leads phosphorus to form derivatives of phosphonic (H 3 PO 3 ) or phosphoric acid (H 3 PO 4 ) in the final products. The factors which control the formation of the products in such cleavage reactions include the structural characteristics of the reactants, path of the reaction followed (mechanism), and the physical conditions applied.…”
Section: Introductionmentioning
confidence: 99%
“…The factors which control the formation of the products in such cleavage reactions include the structural characteristics of the reactants, path of the reaction followed (mechanism), and the physical conditions applied. Both homolytic 12 and heterolytic mechanisms 9 were postulated for such a cleavage, but the mechanism is still not well-understood. 8 This uncertainty of understanding the mechanism of P-C bond cleavage of R-aminophosphonates warrants detailed theoretical studies on such reactions as not much effort has been made in this direction.…”
Section: Introductionmentioning
confidence: 99%